Fishes of Nagpur District, Maharashtra, India - Swapnil S. Ghatge; Sachin W. Belsare; Shrikant S. Jadhav (Journal of Indian Fisheries Association, 2021)
Very few studies are available on fish fauna of Nagpur district. Hence, an attempt was made in the present study to document fishes of Nagpur during the period 2010 to 2016. A total of 75 fish species belonging to 12 orders 28 families and 52 genera have been recorded from Nagpur district during the current study. Cypriniformes was the dominant order represented by 36 species, followed by Silurifomres (15 species), Anabantiformes (8 species) and Synbranchiformes ( 3 species). While Osteoglossiformes, Cyprinodontiformes, Beloniformes, Perciformes and Cichliformes were represented by two species each and Anguilliformes, Gobiiformes and Characiformes were represented by one species each. As per the IUCN Red list of Threatened Species, 51 species were assessed Least Concern whereas 3 species assessed Data Deficient, three species Near Threatened (Bagarius bagarius, Ompok bimaculatus and Anguilla bengalensis), two Vulnerable (Hypselobarbus kolus and Wallago attu) and one species endangered Clarias magur (IUCN 2021). Present study reported 13 new records of fish from Nagpur district and also documented 11 exotic species. The present work will form a basis for further studies and help the student, researchers, planners and policy makers to frame conservation and management strategies.